Media Sosial, Endorsement, dan Diskon dalam Membentuk Perilaku Konsumtif di Lingkungan Ponpes - Holiza, Sri Linda; Saputra, Didin Hadi (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2025)
This study aims to analyze the influence of social media, endorsements, and discounts on the consumer behavior of Islamic boarding school students, as well as to examine the role of religious values ​​and digital literacy as controlling factors in the context of digital consumption. This study uses a quantitative approach with the Partial Least Square–Structural Equation Modeling (PLS-SEM) method through the SmartPLS application. Data were obtained from 102 student respondents in several Islamic boarding schools selected by purposive sampling technique, using a five-point Likert scale questionnaire as the main instrument. The results show that social media has a significant effect on the effectiveness of endorsements and student consumer behavior, while endorsements and discounts are proven to have a positive effect on consumer behavior. In addition, consumer behavior has a moderate effect on interest in discounts, indicating that price promotions are the main drivers of impulsive purchasing decisions. Religious values ​​and digital literacy were found to act as internal controlling factors that reduce the negative influence of social media on consumer behavior. The R² value of 0.487 indicates that this research model has a fairly good predictive ability in explaining student consumer behavior. The conclusion of this study confirms that the consumer behavior of Islamic boarding school students is formed through the interaction between exposure to social media, digital marketing strategies, and the level of internalization of religious values ​​and digital literacy.